The Hidden Curriculum of Artificial Intelligence in Higher Education: Toward Professional Readiness, & Ethical Integration (International Journal of Artificial Intelligence, Computer Science, Management and Technology, 2024)
The integration of artificial intelligence (AI) in higher education is reshaping traditional approaches to learning, teaching, and professional readiness. This paper explores how institutional policies, financial investments, and industry partnerships influence both the explicit and hidden curricula in AI education at R1 universities, including Stanford, MIT, the University of Washington, and the University of Utah. By analyzing programs such as Stanford’s AI4ALL and Utah’s Silicon Slopes partnerships, the study highlights the dual challenges of ensuring equity and fostering ethical awareness while preparing students for AI-driven careers. It examines the hidden curriculum’s role in teaching implicit lessons about collaboration, adaptability, and ethical responsibility, while addressing the disparities in access to AI resources across institutions. Furthermore, the paper connects AI integration with broader questions of authorship, agency, and ethics in disciplines like Writing and Rhetoric Studies. It concludes by proposing strategies for universities to align AI initiatives with inclusive, transparent, and equity-focused policies, ensuring graduates are prepared to navigate the complexities of an AI-driven world responsibly.